Combating the opioid epidemic in the United States - A Simon Pickard; Todd A Lee (BioExcel Publishing Ltd, 2021)
This editorial discusses the series of papers that feature initiatives to mitigate the opioid epidemic in the United States, and challenges encountered during the COVID-19 pandemic.